Customer Satisfaction and Brand Loyalty: A Survey of Nestlé - Waebuesar, Ai-man Esmail; Aruai, Alessa a/p; Rosli, Aina Binti; Mohd Azmi, Ain Najwa Binti (AIBPM Publisher, 2022)
The objective of this paper is to examine the customer satisfaction and brand loyalty of Nestle. As one of the world’s largest food companies, Nestle believes in the power of food to enhance life. The mission of “Good Food, Good Life” means that Nestle aims to provide customers with the best test, and most nutritious product choices in a broad variety of foods and product lineup. Researchers have taken a sample of 100 respondent students since they consume nestle products in the market using the Structural Equation Modeling Approach, the five dimensions of brand loyalty are perceived values, perceived quality, marketing, brand image, and customer expectation are found to have positive effects on customer satisfaction. Data were collected via an online survey through a questionnaire using Google form as primary data. Secondary data was collected from websites and past research papers and articles that showed how customer satisfaction is linked to brand loyalty. To conclude, customer satisfaction is the main key to the expansion of brand loyalty and retaining customers. Keywords: Brand Loyalty, Customer Nestle, Satisfaction.